Mosquitoes in the Danube Delta: searching for vectors of filarioid helminths and avian malaria - Ionică, Angela Monica; Zittra, Carina; Wimmer, Victoria; Leitner, Natascha; Votýpka, Jan; Modrý, David; Mihalca, Andrei Daniel; Fuehrer, Hans-Peter (Parasites & vectors, 2017)
BACKGROUND: Mosquitoes are arthropods of major importance to animal and human health because they are able to transmit pathogenic agents such as filarioids (Spirurida), vector-borne nematodes, which reside in the tissues of vertebrates. In Europe, recent research has mostly focused on mosquito-borne zoonotic species, while others remain neglected. Mosquitoes are also vectors of avian malaria, which has an almost worldwide distribution, and is caused by several Plasmodium species and lineages, the most common being P. relictum. The Danube Delta region of Romania is one of the most important stopover sites for migratory birds. The local mosquito fauna is diverse and well represented, while filarial infections are known to be endemic in domestic dogs in this area. The aim of the present study was thus to assess the potential vector capacity for various filarial helminths and avian malaria of mosquitoes trapped in the Danube Delta. METHODS: In July 2015, mosquitoes were collected at seven sites located in and around a rural locality in the Danube Delta region of Romania, using CO2-baited traps and hand aspirators. Additionally, a trap was placed next to a microfilaremic dog co-infected with Dirofilaria repens and D. immitis. All randomly trapped mosquitoes were identified to the species level and pooled according to date, sampling site, and taxon. Three hundred individual mosquitoes sampled next to the microfilaremic dog were processed individually and divided into abdomen and thorax/head. Following DNA extraction, all samples were screened for the presence of DNA of filarioid helminths and avian malaria agents by PCR techniques. RESULTS: All 284 pools (a total of 5855 mosquitoes) were negative for filarioid DNA. One pool of Culex modestus mosquitoes was positive for Plasmodium sp. lineage Donana03. In the individually extracted mosquitoes, one abdomen of Aedes vexans was positive for D. repens DNA, one thorax/head of Ae. vexans was positive for DNA of Setaria labiatopapillosa, and two thorax/head of Cx. pipiens f. pipiens were positive for P. relictum lineage pSGS1. CONCLUSION: The present study suggests the vector competence of Cx. modestus and Cx. pipiens for avian Plasmodium including pathogenic species P. relictum and Ae. vexans for mammalian filarioids. Moreover, it indicates the role of Cx. pipiens f. pipiens as a potential natural vector of P. relictum lineage pSGS1 in nature.
Keywords: Culicidae; Avian malaria; Malaria, Avian; Mosquito vectors; Animals; Aedes; malárie ptačí; Culex; Filarioidea; Humans; psi; filarióza; Plasmodium; Filariasis; Danube Delta; Dirofilaria repens; Setaria (Nematoda); hmyz - vektory; Filarioids; Rumunsko; zvířata; Insect Vectors; Dogs; Romania; Dirofilaria immitis; lidé; Setaria Nematode